Investigating elementary school pupils’ proficiency in mastering English vocabulary - Diana Achmad (Studies in English Language and Education, 2014)
English has been taught at elementary schools as one of the local content subjects. It is necessary to study English from an early age in order to achieve good mastery in it. To master English means to master the four skills in it and also the language aspects, including vocabulary. As one of the language aspects, vocabulary plays an important role in language learning. This study reports on pupils’ proficiency in mastering English vocabulary after three years of studying in elementary school. The writer chose 55 grade-four pupils of SD Methodist Banda Aceh as a sample for this study. They were given a vocabulary test related to reading and writing skills consisting of 26 items. The test was to be done in 20 minutes. After calculating the data, it was found that the mean score (x) of the pupils was 69.5, with the highest score at 92.3 and the lowest score at 26.9. More than 50% of the pupils could answer the questions correctly in less than 20 minutes. Only 4 out of the 55 pupils answered the questions less than 50% correctly and no one answered 100% correct. According to these results, this study showed that the pupils achieved good proficiency in vocabulary.